2010
DOI: 10.1186/1465-9921-11-75
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of cell-mediated airways diseases

Abstract: "Inflammation resolution" has of late become a topical research area. Activation of resolution phase mechanisms, involving select post-transcriptional regulons, transcription factors, 'autacoids', and cell phenotypes, is now considered to resolve inflammatory diseases. Critical to this discourse on resolution is the elimination of inflammatory cells through apoptosis and phagocytosis. For major inflammatory diseases such as asthma and COPD we propose an alternative path to apoptosis for cell elimination. We ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 146 publications
0
18
0
2
Order By: Relevance
“…DE exposure induced a decrease in mast cell staining in the epithelium. This could reflect either: (a) a mast cell migration from the epithelium to the airway lumen (Persson & Uller, 2010) or to lymph nodes (Dabak et al, 2004) or (b) a degranulation of tryptase from mast cells (Amin, 2012). However, there were no increases in mast cell numbers detected in airway lavages and no other signs of an aggravated allergic inflammation, such as airway eosinophilia, allergic symptoms or increased airway permeability (measured as BW albumin).…”
Section: Discussionmentioning
confidence: 89%
“…DE exposure induced a decrease in mast cell staining in the epithelium. This could reflect either: (a) a mast cell migration from the epithelium to the airway lumen (Persson & Uller, 2010) or to lymph nodes (Dabak et al, 2004) or (b) a degranulation of tryptase from mast cells (Amin, 2012). However, there were no increases in mast cell numbers detected in airway lavages and no other signs of an aggravated allergic inflammation, such as airway eosinophilia, allergic symptoms or increased airway permeability (measured as BW albumin).…”
Section: Discussionmentioning
confidence: 89%
“…Also, rats are reported to be more sensitive than mice to the pulmonary toxic effects induced by nano-TiO 2 (Bermudez et al, 2002). We have considered the possibility, as suggested by Persson & Uller (2010), that inflammatory cells might persist in the lung interstitium during lung disease/ injury instead of migrating towards the airway lumen, therefore decreasing the number of leukocytes found in BAL fluid. However this hypothesis was rejected following lung histology analyses, which showed that the level of inflammation in the lungs was proportional to BAL cellular results.…”
Section: Discussionmentioning
confidence: 95%
“…We repeat this cautionary note in an extended review on resolution of cell-mediated respiratory diseases where we discuss a role of egression in the elimination not only of granulocytes and lymphocytes but also of mast cells and dendritic cells 2. We further discuss how elimination of leucocytes through egression can be compatible with the use of sputum cell counts to adjust treatment in asthma 1.…”
mentioning
confidence: 89%